Motif Mengunggah Foto Selfie ke Dalam Media Sosial Instagram di Kalangan Remaja SMAN 1 Denpasar - Lestari, Lidya Mulya; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
ABSTRA CT   Selfie is an act of taking self-photograph by using electronic devices. The initial use of this selfie word is Selca or Self-Camera. In 2013, Selfie is officially listed as a known word on the Oxford English Dictionary that define an activity of taking self-photograph using electronic devices and shared via social media. The aim of this research is to describe the motives of adolescents from SMAN 1 Denpasar in performing the act of selfie and share it to Instagram. This research used descriptive quantitative approach, informants were obtained by using purposive sampling technique, and data were obtained by distributing questionnaires. The several stages of analyzing techniques used in this research are statistical data analysis techniques of frequency distribution, cross tabulation with data processing using SPSS program computational calculation and conclusions drawing. The results shows that adolescents tend to have a motive to get response such as like, while the adolescent is less likely to have the motive of recognition in the form of desire to get attention. More teenage girls tend to have motives of getting new experiences and motives to get responses when compared to boys, while there is less significance difference between women and men in terms of motives of getting recognition.   Keywords : Adolescent, Instagram, Motives, Selfie